IMPLANTATION OF SUPERIOR VENA CAVA FILTERS - S. A. Prozorov (Неотложная медицинская помощь)
Abstract The purpose of this review is to evaluate the results of superior vena cava filters placement in order to prevent pulmonary embolism associated with upper extremities deep vein thrombosis. The central venous catheter, malignancy and lower extremities deep venous thrombosis are main risk factors of upper extremities deep venous thrombosis. The placement of the superior vena cava filter is a safe and effective method for preventing pulmonary embolism in patients with acute upper extremities deep vein thrombosis where therapeutic anticoagulation is contraindicated or appeared to be ineffective.